Biotransformation of okara extracted protein to nanocellulose and chitin by Gluconacetobacter xylinus and Bacillus pumilus. (February 2022) - Taokaew, Siriporn; Nakson, Nawachon; Zhang, Xingkai; Kongklieng, Passana; Kobayashi, Takaomi
Abstract: To sustainably obtain nanocellulose and chitin of high economic value, use of protein extracted from Okara waste as a single Nitrogen source in cultivations of Gluconacetobacter xylinus and Bacillus pumilus were assessed. Among the tested concentration (0–3%w/v) of the protein, the high conversion of a Carbon source to nanocellulose fibers ( 50%) was achieved, when the culture medium contained 2–3% of the protein. For chitin produced from crab shell fermentation, similar yield and degree of acetylation were obtained regardless of the protein concentration, but chitin purity was high under the fermentation containing 1.5%w/v protein due to the highest protease activity (170 U/ml). At the optimum concentration of okara extracted protein, the biosynthesized nanocellulose and chitin fermentative product had high molecular weights of 9.2 and 2.4 × 10 6 g/mol, respectively. Valorization of okara waste to nanocellulose and chitin could potentialize a non-value resource resulting in economic profit. Graphical abstract: Unlabelled Image Highlights: Highly pure nanocellulose and chitin were successfully biologically produced. Increase in extracted protein concentration resulted higher yield of nanocellulose. Extracted protein at 1.5%w/v yielded high content of protease used in fermentation. High crystallinity and molecular weight of nanocellulose and chitin were obtained.